Analisis Persaingan Produk Indomie & Mie Sedaap - Nurdianty, Salsabila; Latifah, Nuraeni; Hidayat, Syamsul (Jurnal Ilmu Manajemen, Bisnis dan Ekonomi, 2023)
The era of globalization has demanded changes in the field of marketing. The increasing level of competition in local and global business and conditions of uncertainty force companies to achieve competitive advantages in order to be able to win competition in global business. The development of instant noodle products has led to increasingly fierce competition, instant noodle manufacturers are trying to market their products by carrying out intensive promotions to offer the superiority of their products. There are two big brands that dominate the instant noodle market share, namely Indomie and Mie Sedaap. The aim of the research is to analyze Indomie's competition with Mie Sedaap. So you can find out how buyers make decisions when purchasing instant noodles. The method used in this research is a quantitative method with sampling generally carried out randomly, data collection using research instruments, data analysis is quantitative or statistical in nature with the aim of testing hypotheses that have been determined late. Researchers took a sample of 384 respondents by distributing questionnaires. Based on the statistical test results of the 3 variables, it was found that the results of this descriptive statistical test produced a number <1, namely 0.728 for P1 and P2 and 0.924 for P3 respectively, so the results of this test were appropriate because the resulting standard deviation value did not have a significant difference from the average value. -average. The results of the correlation test state that if the significance value (Sig) is <0.05 then the test results are valid. In this study, the three variables had a Sig value of <0.001. Then for the reliability test results, a value of 0.826 was obtained and it was declared reliable. Finally, for the results of the independent sample T test, the respective Sig values were 0.269 for P1 and P2, while for P3 it was 0.825, so it can be concluded that there is no difference between these three variables. Based on this explanation, the majority of the 384 respondents chose Indomie as the instant noodle product of choice. then regarding product quality the majority answered that there was no difference in product quality. then based on the attractiveness of the advertisement the majority strongly agree and finally based on the product price there is no difference.